Fall River outrage : life, murder, and justice in early industrial New England - Kasserman, David Richard (Philadelphia : University of Pennsylvania Press, 1986)
Fall River Outrage recounts one of the most sensational and widely reported murder cases in early nineteenth-century America. When, in 1832, a pregnant mill worker was found hanged, the investigation implicated a prominent Methodist minister. Fearing adverse publicity, both the industrialists of Fall River and the New England Conference of the Methodist Episcopal Church engaged in energetic campaigns to obtain a favorable verdict. It was also one of the earliest attempts by American lawyers to prove their client innocent by assassinating the moral character of the female victim. Fall River Outrage provides insight in American social, legal, and labor history as well as women's studies.
1. The Outrage 5 -- 2. Beginning a Life in the Mills 29 -- 3. Ending a Life in the Mills 51 -- 4. The Minister 75 -- 5. Preliminary Engagements 99 -- 6. The Prosecution 133 -- 7. The Defense 159 -- 8. The Verdict 187 -- 9. Public Justice 213.
Includes bibliographical references (pages 255-272) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Avery, Ephraim K., -- 1799-1869 -- Trials, litigation, etc; Cornell, Sarah Maria, -- 1802-1832.; Cornell, Sarah Maria, -- 1802-1832.; Avery, Ephraim K., -- d. 1869 -- Trials, litigation, etc; Avery, Ephraim K., -- -1869.; Cornell, Sarah Maria, -- 1802-1832.; Avery, Ephraim K., -- 1799-1869; Cornell, Sarah Maria, -- 1802-1832; Trials (Murder) -- Rhode Island -- Newport; Working class -- Massachusetts -- Fall River -- History; Procès (Meurtre) -- Rhode Island -- Newport; Travailleurs -- Massachusetts -- Fall River -- Histoire; HISTORY -- United States -- 19th Century; Working class -- Massachusetts -- Fall River -- History; Trials (Murder) -- Rhode Island -- Newport; Trials (Murder); Working class; Massachusetts -- Fall River; Rhode Island -- Newport; Mord; Strafverfahren; USA; Geschichte 1800-1850.; Trial and arbitral proceedings; History; Trials, litigation, etc; Trial and arbitral proceedings; Comptes rendus de procès et d'arbitrage.